A multidisciplinary guideline-based approach to improving the sudden cardiac arrest care pathway: The Copenhagen framework - Mette Kirstine Wagner; Jan Christensen; Kate Allen Christensen; Camilla Dichman; Rikke Gottlieb; Ida Kolster; Carolina Malta Hansen; Helle Hoff; Christian Hassager; Fredrik Folke; Bo Gregers Winkel (Resuscitation Plus, 2024)
Although recommended in the European Resuscitation Council (ERC) and European Society of Intensive Care Medicine (ESICM) Guidelines, a framework for delivering post-cardiac arrest care in a systematic manner in dedicated high-volume cardiac arrest centers is lacking in the existing literature.To our knowledge, the Copenhagen Framework is the only established framework of its kind. The framework comprises management of out-of-hospital cardiac arrest (OHCA) survivors, and follow-up, and rehabilitation. The framework also incorporates research projects on cardiac arrest survivors and their close family members. The overall aim of this paper is to describe a framework made in order to bridge the gaps between international recommendations and delivering high-quality post-resuscitation clinical care, improving the continuity of care for OHCA survivors, access to post-CA rehabilitation, a seamless transition to everyday life, and ultimately patient outcomes in the future.